The Implications of Absorption Cost Accounting and Production Decisions for Future Firm Performance and Valuation* - GUPTA, MAHENDRA; PEVZNER, MIKHAIL; SEETHAMRAJU, CHANDRA (Contemporary Accounting Research, 2010)
We examine how inventory overproduction among high fixed costs firms affects these firms’ contemporaneous and future accounting performance, and how financial analysts and the stock market incorporate implications of these relations in their reactions. We find that higher fixed costs firms engaging in opportunistic overproduction are able to increase their contemporaneous return on assets (ROAs), but only those higher fixed costs firms that also experience inventory increases, sales declines, and issue common stock also experience declines in their future accounting performance. We further find that financial analysts are aware of this phenomenon and appropriately reduce their forecasts of future earnings per share (EPS) for higher fixed costs firms that experience sales declines and inventory increases. In general, we do not find that the stock market penalizes such opportunistic overproduction.